Expertise in soccer teams: A thematic inquiry into the role of Shared Mental Models within team chemistry. (May 2016) - Gershgoren, Lael; Basevitch, Itay; Filho, Edson; Gershgoren, Aaron; Brill, Yaron S.; Schinke, Robert J.; Tenenbaum, Gershon
Abstract: Aims: The purpose of the current study was to establish a conceptual framework of team chemistry components in sport with an emphasis on Shared Mental Models (SMM). Method: Elite soccer coaches (n = 6) and players (n = 3) were interviewed using a semi-structured interview guide. An inductive thematic analysis was employed to analyze the data. Results: Four themes related to team chemistry components were identified: (1) members' characteristics (i.e., demographic data, on-field characteristics, and member's ego), (2) coach–players interactions (i.e., professional interaction and emotional intelligence of coaches), (3) interactions among the players (i.e., professional understanding, efficacy beliefs, team cohesion, players' emotional intelligence, team roles, and goals), and (4) interactions with environmental factors (i.e., owners, management, fans, and media). Conclusions: The cognitive components of the team chemistry model were clustered to establish a conceptual framework of SMM. Furthermore, the cognitive-affective-social-behavioral linkage of team chemistry and athletic performance is examined in light of the emerged model and conceptual framework. Implications and future directions are also discussed. Highlights: A four-theme model emerged for Team Chemistry (TC). TC can be captured via cognitive, affective, and social lenses. TC & Shared Mental Models (SMM) are perceived to effect performance in elite level. SMM consists of 3 dimensions: general & situational cognition, and efficacy beliefs.